Intravascular Ultrasound Imaging for Evaluation of Aortic Elastic Properties: Review of the Literature and a Single-Center Experience - Mileva, Niya Boykova; Vassilev, Dobrin Iotkov (Cardiology and Cardiovascular Medicine, 2020)
Introduction: Aortic stress is a well-known cardio-vascular risk factor. For years, different methods have been studied in the assesment of aortic elastic properties and large arterial stiffness for risk stratification. We asses the role of intravascular ultrasound imaging for the evaluation of aortic elastic properties. Methods: Intravascular ultrasound imaging of the aorta was performed in 12 patients with transthoracic echocardiography (TTE) and computed tomography (CT) evidence for enlargement of the ascending aorta – diameter ≥ 40.0 mm. Mechanical properties of the aorta were derived from the measured diameters and intra-aortic pressure. Paired samples T-test analysis was performed to determine difference between measurements derived by TTE, CT and IVUS. Results: Mean values of the calculated elastic properties of the ascending aorta were as follows: compliance 0.021 ± 0.02; strain 205 ± 4.3; aortic stiffness index 4.3 ± 0.75; elastic modulus 0.31 ± 0.05. On paired T-test analysis maximum ascending aortic diameter measured by CT aortography and IVUS did not differ significantly (t = -0.19, p=0.985), but a significant difference between IVUS measurements and TTE derived diameters was found (t = 13.118, p = 0.034). On average, IVUS diameters were 4.1 mm larger than the results acquired by TTE (95% CI [14.21, 17.13]). Conclusion: IVUS examination of the ascending aorta provided larger diameters than the ones collected by means of TTE. However, IVUS measurements did not differ significantly from diameters derived by CT aortography.